Eastern Lithuanian (Utena) i-Stem Nouns - Rinkauskienė, Regina (Kalbotyra, 1997)
The article deals with the morphological problems of one of the Eastern Lithuanian dialects. It investigates the fusion of i-stem nouns with ė and i̭o-stem nouns. The analysis shows that the fusion in the stems was influenced by the phonetic development of the dialect, the gender of the noun and the stress. The formation and abundance of homonymic forms determine the disappearance of the rare masculine nouns of mixed declination and their transition to the class of feminine nouns. The material presented demonstrates the polarisation of case types according to gender.